Pengaruh Diversitas Dewan Direksi Terhadap Kinerja Perusahaan - Lindhiasari, Sherlyntang; Muazaroh, Muazaroh (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This study aims to investigate the influence of board diversity on the performance of banking sector companies listed on the Indonesia Stock Exchange (IDX). The research employs a quantitative approach. The data used is obtained from the financial reports and annual reports of banking sector companies listed on the Indonesia Stock Exchange (IDX). The sample for this study consists of banking sector companies listed on the Indonesia Stock Exchange during the period 2020-2022. The analysis technique used is multiple linear regression. The results of the study indicate that age and nationality diversity have a significant negative impact on company performance. Gender diversity and tenure do not have a significant impact. The implications of these research findings for the banking sector suggest that when selecting a board of directors, diversity in terms of age and nationality should be avoided as it may lead to a decline in company performance.